The Impact of Transformational Leadership on Organizational Commitment and Intention to Stay: Empirical Evidence From China’s Performing Arts Industry - Xu, Hengzhe; Wang, Zhong; Lian, Naiyu; Khan, Asif; Zhang, Lei (Frontiers in Psychology, 2022)
As a part of the cultural industries, performing arts has been playing an important role in enriching people's spiritual life, leveling culture and education, creating jobs and even making economic benefits. Numerous psychological and behavioral studies have been performed on transformational leadership (TL), nevertheless, these studies did not focus on performing arts industries. This implies that a significant methodology is required to tackle the complicated concepts of TL and social factors in a performing arts industries context. This paper aimed to observe the direct impacts of transformational leadership on organizational commitment (OC). Furthermore, it examined the indirect effects of transformational leadership on organizational commitment and intention to stay (ITS), via person-job fit (PJF), social capital (SC) and psychological capital (PC). As the results of this research, TL was discovered to have a positive impact on OC and person-job fit, while having no significant effect on ITS. Furthermore, PJF had a significant impact on SC. Moreover, SC significantly influenced PC. In addition, PC was discovered to be in a significant correlation with OC, while having no significant association with ITS. Finally, OC was also in a significant relationship with ITS.